The development of knowledge management system for public higher learning in collaborative environment using Lotus Notes software - Abdullah, Rusli (2004)
In higher learning institution sectors,collaboration tools of Knowledge Management Systems (KMS) explore the opportunity to create, gather, access, organize, distribute and disseminate the knowledge to their community of practice for many purposes such as learning process, R & D and others.This paper describes the theoretical concept and approach of knowledge management system (KMS) that could be implemented in Public Higher Learning Institution (PHLI) by showing how the framework of knowledge management system model is developed using Lotus Notes software.The achievement of this KMS framework is an added value for any PHLI that needs to implement the KMS, which can help them to achieve their aims and objectives.The emphasis also will be given to the activities that may be of concern for each stage in the KM life cycle by including the critical success factors (CSF) to ensure that KMS initiatives will deliver competitive advantages to the organization.